2020
DOI: 10.5812/ijpbs.96715
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cognitive Behavioral Therapy on Anxiety and Depression in Iranian Infertile Women: A Systematic and Meta-Analytical Review

Abstract: Context:The prevalence of infertility, as one of the most unpleasant experiences, is approximately 13.2% in Iran. It can affect the quality of life in infertile people through mental disorders, such as depression and anxiety. Objectives: This systematic review was carried out to assess the effect of cognitive-behavioral therapy (CBT) on anxiety and depression of infertile women in Iran. Data Sources: All articles published in English and Persian until 20 February 2019 in databases, including Magiran, Iranmedex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…While diagnosing the infertility-cause stresses and damages, psychological interventions help infertile couples work through their problems and adapt to infertility [ 16 ]. Several studies showed that socio-psychological interventions for couples undergoing infertility treatments can effectively reduce mental health problems and improve clinical pregnancy rate [ 17 , 18 ]. Cognitive-behavioral therapy is a highly efficient short-term treatment in psychology that focuses on modifying dysfunctional behaviors and thoughts to help individuals experience general mental health [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…While diagnosing the infertility-cause stresses and damages, psychological interventions help infertile couples work through their problems and adapt to infertility [ 16 ]. Several studies showed that socio-psychological interventions for couples undergoing infertility treatments can effectively reduce mental health problems and improve clinical pregnancy rate [ 17 , 18 ]. Cognitive-behavioral therapy is a highly efficient short-term treatment in psychology that focuses on modifying dysfunctional behaviors and thoughts to help individuals experience general mental health [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…While diagnosing the infertility-cause stresses and damages, psychological interventions help infertile couples work through their problems and adapt to infertility (16). Several studies showed that sociopsychological interventions for couples undergoing infertility treatments can effectively reduce mental problems and improve clinical pregnancy rate (17,18). Cognitive-behavioral therapy is a highly e cient short-term treatment in psychology that focuses on modifying dysfunctional behaviors and thoughts to help individuals experience general mental health (19).…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Having a child is associated with many positive values such as emotional benefits, economic and security interests, a sense of worth and survival, and is highly valued in a variety of cultures. [ 4 5 6 ] Previous studies in Iran have shown that most couples have a strong desire to have children and often consider it necessary to have at least one child in order to maintain the strength of their lives. [ 7 ] However, many people around the world suffer from infertility.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] However, many people around the world suffer from infertility. [ 8 ] In fact, infertility causes a crisis in various aspects of a couple's life[ 5 6 ] and can have a significant impact on the couple's emotional functioning. [ 6 8 ] However, the entry of a child into the cold family can improve the couple's communication and ultimately solve the psychological problems caused by the child's vacuum in their lives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation